Analisis Dampak Pandemi COVID-19 Terhadap Pembiayaan Bank Syariah Mandiri (BSM) dan Dana Pihak Ketiga - Wildan Zaky; Muhammad Farih Fuadi; Robby Asalukar Ridlo; Endang Kartini Panggiarti (Global Leadership Organizational Research in Management, 2024)
This article discusses the consequences of the Covid-19 pandemic on financing and third party funds at Bank Syariah Mandiri (BSM). The focus is to highlight the obstacles faced by the Islamic banking industry due to the impact of the pandemic, as well as the need for creative and innovative strategies to accommodate change and maintain continuity. This pandemic has affected the role of sharia banking as an intermediary, especially in terms of providing credit and recovering third party funds. Bank Mandiri Syariah experienced fluctuations in financing and third party funds from January to March 2020, due to a decrease in funding demand and economic uncertainty. To face this challenge, Bank Syariah Mandiri and other sharia banking institutions are adopting operational strategies that involve digitalization and technology. Digitalization is considered a crucial step in providing banking services during the pandemic. The aim of this research is to assess the operational tactics used by sharia banks to fulfill their role as mediators during the pandemic, as well as the impact of the Covid-19 pandemic on financing and third party funds at Bank Syariah Mandiri.